The use of antivirals for influenza prophylaxis a review of the clinical effectiveness - Chao, Yi-Sheng; Spry, Carolyn; Canadian Agency for Drugs and Technologies in Health (Ottawa (ON) CADTH, 2017)
Influenza is seasonal and usually caused by the influenza A or B virus. It is a major disease burden leading to more than 5% of adults and 20% of children being infected annually. Pandemic influenza can occur while a new strain of virus becomes the cause of infection, such as influenza 2009A/H1N1. Vaccination can be effective in controlling influenza transmission. However, there are several factors that influence the effectiveness of vaccinations, including improper matching between vaccine and virus strains, antigenic drifts and inadequate vaccine coverage. In addition to vaccination, antivirals are used orally or through other routes at an earlier stage to prevent infection and transmission of the influenza. Antivirals inhibit virus replication, and the decrease in virus shedding within infected individuals may be the reason of reduced transmission. Unlike vaccination, antivirals need to be stockpiled for influenza prevention or treatment. The cost of storage and the uncertainty in the effectiveness warrant further review of the effectiveness of antivirals on influenza prophylaxis. This review aims to update the 2010 Rapid Response report by summarizing the recent literature on the effectiveness of antivirals on influenza prophylaxis
Includes bibliographical references
Keywords: Influenza, Human / immunology; Comparative Effectiveness Research; Antiviral Agents / therapeutic use; Treatment Outcome; Influenza, Human / prevention & control; Influenza Vaccines / therapeutic use